The teaching of the Educational Policy and implications in the initial teacher training - Gabriela Gamberini (Red Latinoamericana de Estudios Epistemológicos en Política Educativa, 2018)
This article analyzes and reflects on the development of a syllabus on educational policy that is part of the curricula of two teaching careers inserted in a public university in Argentina. It addresses topics related to the selection of the knowledge content to be taught, methodological definitions, and the characteristics of the process of appropriation of contents by students. It also identifies problematic learning issues that highlight the foundations of the teaching proposal and the premises that support the professional profile of teacher training. The analysis focuses on the emergence and development of the field of educational policy and its implications for teaching, valuing reflection processes in university education.